Pengaruh Popularitas BTS Sebagai Brand Ambassador Tokopedia dan Brand Associations Terhadap Brand Loyalty Pelanggan Tokopedia Kalangan Gen-Z - Naura Kamila Prasetyanti; wiwid Noor Rakhmad; Tandiyo Pradekso (Interaksi Online, 2022)
Tokopedia has collaborated with BTS since 2019 and is still going on until now. Tokopedia makes BTS as its brand ambassador because of the high popularity of BTS. Tokopedia and other e-commerce companies are competing to be the best. Based on data released by iPrice, from 2020 to 2021, Tokopedia rose to rank one as the most visited e-commerce. However, based on data from Top Brand Award 2021, Tokopedia experienced a decrease in numbers in 2021 compared to the previous year, for the Top Brand for Gen-Z Index category. With the drop number in Top Brand Index, the level of customer loyalty is questionable. This study aims to explain the influence of the popularity of BTS as Tokopedia brand ambassador and brand associations on the brand loyalty of Tokopedia customers among Gen-Z. The theory used is Source Attractiveness Model and Brand Relationship Theory. The sample of this study consisted of 100 respondents aged 13 – 27 years old, knowing BTS as a Tokopedia Brand Ambassador, had made a purchase using Tokopedia at least in the last one year. The sampling technique used is non-probability. The results of this research indicate that the popularity of BTS as Tokopedia's brand ambassador on the brand loyalty of Tokopedia customers among gen-Z has a significance value of 0.017 < 0.05, which means it has an influence. This shows that Source Attractiveness Model can be applied. Meanwhile, brand associations on the brand loyalty of Tokopedia customers among gen-Z have a significance value of 0.002 < 0.01, which means it has an influence. This shows that Brand Relationship Theory can be applied.